I learn for my hobby: How much are aquarists satisfied? - (:unkn) unknown (Sakarya University, 2015)
Since smart devices provide mobility convenience, in the field of information technology the need to popularize software applications for mobile/smart devices has emerged. Despite of these developments, web applications still maintain their importance. Therefore, IT (Information Technologies) studies are carried out by paying regard to the both situations for software developers. © The Turkish Online Journal of Educational Technology.